Živočíšne lipoxygenázy – štruktúra, polohová špecifita izoenzýmov lipoxygenáz a ich význam - Bezáková, Lýdia; Holková, Ivana; Balažová, Andrea; Obložinský, Marek; Mikuš, Peter (Chemické listy, 2017)
Lipoxygenases (LOX) constitute a heterogeneous family of lipid peroxidizing enzymes which catalyze the stereospecific insertion of molecular oxygen into polyunsaturated fatty acids. The primary products of LOX reaction are hydroperoxy fatty acids, which are rapidly reduced to the corresponding hydroxy derivatives. In mammalian organisms, there are 4 main LOX isoforms, 5-LOX, 8-LOX, 12-LOX, 15-LOX, constituting hydroperoxides with positional and stereo specificity. In the subsequent metabolic processes they provide significant cell signaling molecules and secondary messengers taking part in the development of inflammatory, tumorous and other diseases. Recent studies clarified the role of lipoxygenases in various diseases. The study of the structure and the active site of enzyme, preparation of recombinant forms with the targeted gene mutations have shown possibilities for better understanding the lipoxygenase role in various pathological processes. Searching for selective inhibitors of LOX isoenzymes is an active area of investigation. They can represent an important research tool or become a promising targeted therapy of a wide range of human diseases.
Keywords: Lipoxygenases; lipoxygenasy; Mutation; Arachidonic Acid; Fatty Acids, Unsaturated; zvířata; izoenzymy; Isoenzymes; lidé; nenasycené mastné kyseliny; molekulární konformace; Mammals; savci; Humans; mutace; kyselina arachidonová; Molecular Conformation; Animals